PEER REVIEW IN UNIVERSITY COURSES - Vera S. Kharchenko (Высшее образование в России)
The article presents the experience of using the method of peer review by higher school students. One of the common definitions of peer review is a «mutual assessment» and «assessment of colleagues». Peer review is used in various spheres, including education (especially remote, online-education). On the basis of the reviews prepared by the students after the completion of the course «Sociology of Employment» (2013-2015), the author analyzes the possibilities and limitations of this method. The advantages of the method are the reflection of the task and requirements to its fulfilling, the greater responsibility, the better quality ofanalytic work, objectivity in assessment ofcolleagues' intellectual product, mastering of academic writing. Nevertheless, the positive effect of peer review in the organization of individual work may be reduced by excessive labour input in its implementation. The author offers advice on the implementation of the mutual review into the practice of teaching and the organization of higher school students' individual study.